Structural failures due to anthropogenic sinkholes in the urban area of Naples and the effect of a FRP retrofitting. (1st January 2017) - Cennamo, Claudia; Angelillo, Maurizio; Cusano, Concetta
Abstract: This work is about the hypothesis of structural health monitoring of architectural heritage in masonry exposed to collapse risk in the city of Naples. We analyze the collapse mechanisms in static terms relating the planimetric layout of the underground cavities of Naples with some recent collapses of structures that occurred in the city. The present work focuses on the relationship between these collapses and the presence of underground cavities. Constructions in masonry, contrary to common opinion, are structures that provide comparatively level of safety depending on to the strength of materials and construction techniques adopted, together with the fact that they are able to settle and to find a new equilibrium configuration; in other words they embody the prototype of resilient structures. The main critical issue able to put in crisis a huge masonry building is the subsoil subsidence. In fact, the structure reaches the collapse for the creation of cavities or chasms under it, which literally remove the support surface of its foundation. In particular, the present work aims to analyze the collapse of two buildings of the Department of Veterinary Medicine of Federico II, that occurred in Naples last December and, starting from a real case of the collapse of a masonry building, the research aims to correlate this collapse with one of the cavities present in the subsoil of Naples and evaluate the possibility that the cause of the collapse to be related the corresponding cavity (or to a newly formed) situated below a corner of the building. The effect of a possible retrofitting intervention, consisting in three FRP strips glued to the surface of the structure, is also considered.